Inequality and productive structure: New evidence at the world level - Verónica Amarante; Bibiana Lanzilotta; Joaquín Torres (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper investigates the evolution of the productive structure around the world and the role it plays in the difference in inequality levels, using panel data for the period from 1995 to 2018. We approximate a country's productive structure through the Economic Complexity Index. Our results indicate that income inequality at the world level is not linearly related to economic complexity. Instead, our results indicate that, when the levels of complexity of the economy are very low, increases in complexity mainly lead to an increase in economic inequality. At higher levels of economic complexity, the effect of economic complexity on income inequality becomes negative. This means that economic complexity becomes equality enhancing after certain thresholds, which seems to reflect the situation in high-income economies.
Keywords: O11; O15; 330; income inequality; productive structure; economic complexity; panel data